Cockfighting in Javanese Muslim Society during the Nineteenth and the Early Twentieth Century (JOURNAL OF INDONESIAN ISLAM, 2021)
This study aims to analyze the thoughts of Javanese Muslims on cockfighting in the nineteenth and the early twentieth centuries. It has been a custom and culture since humans domesticated chickens. At first, it had a sacred connotation. It eventually devolved into a profane gamble. Although Islam banned animals fighting and gambling, the tradition continued during the Islamic era. This study examines (1) the reasons why Javanese Muslim culture enjoys cockfighting, (2) the forms of Javanese Muslim thought about cockfighting in Javanese manuscripts from the nineteenth and the early twentieth centuries, (3) its influence on colonial and royal rule in Java. Research showed that some thoughts normalized cockfighting and cockfight gambling, but some viewed the game as an evil deed during the nineteenth and the early twentieth centuries.